Heurísticas do design em jogos digitais: o caso League of Legends - Vieira, Guilherme Sousa (2018)
The present master's thesis had as its objective a research on the League of Legends game, exploring its design philosophies to identify and discuss within the heuristic theme in game design, using as base the heuristic evaluation of the reworking of one of its characters, the champion Xerath. We start by dissolving the game LoL, how it occurs, how it was in its initial form, how to put the philosophy of work of its developer studio and then we go to the description of the game in its technical and playful aspects. In the sequel we delve into the discussion of heuristics, identity & aesthetics in digital games, where we have developed on top of researched authors, especially the texts of Brenda Laurel, Sherry Turkle and James Paul Gee acquiring a basis for the heuristic evaluation of the character. Next, we focus on the contextualization of the character who came to be evaluated, the champion Xerath, his birth, his involvement with the author and his status before and after the reworking. In its final part, this research retakes the discussed points and applies the heuristic evaluation in the changes that occurred in the character, after that, the process of extrapolation of the work begins and final considerations